1993
DOI: 10.1111/j.1398-9995.1993.tb02167.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of eosinophils in the pathogenesis of atopic dermatitis ‐ eosinophil granule proteins as markers of disease activity

Abstract: Currently, there is a large body of evidence that atopic dermatitis (AD) has an Immunologic basis. Atopy‐specific helper T cells (Th2‐like T cells) may play a pathogenetic role by producing and releasing cytokines relevant for the allergic inflammation, such as IL‐4, IL‐5, and other growth factors. Eosinophils are believed to be of major importance as effector cells mediating the pathogenetically relevant late‐phase reaction which is associated with a significant destruction of the surrounding tissue. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1
6

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(93 citation statements)
references
References 38 publications
4
82
1
6
Order By: Relevance
“…The number of eosinophils and neutrophils decreased prior to amelioration of dermatitis. Since eosinophils are inflammatory cells, which in part form dermatitis (Liferman et al, 1985;Kapp, 1993;Liferman, 1994), it is conceivable that the decrease in their number is one of the reasons for the ameliorative effect. Previous studies reported that a low calorie diet or fasting causes a reduction in the number of neutrophils in the peripheral blood (Powanda, 1977), so that, a low calorie diet may also be related to a reduction in the number of eosinophils, although it has not been demonstrated previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of eosinophils and neutrophils decreased prior to amelioration of dermatitis. Since eosinophils are inflammatory cells, which in part form dermatitis (Liferman et al, 1985;Kapp, 1993;Liferman, 1994), it is conceivable that the decrease in their number is one of the reasons for the ameliorative effect. Previous studies reported that a low calorie diet or fasting causes a reduction in the number of neutrophils in the peripheral blood (Powanda, 1977), so that, a low calorie diet may also be related to a reduction in the number of eosinophils, although it has not been demonstrated previously.…”
Section: Discussionmentioning
confidence: 99%
“…In order to clarify the mechanisms through which skin inflammation was suppressed, the number of eosinophils, which are inflammatory cells playing a major role in the development of dermatitis and skin irritability (Liferman et al, 1985;Kapp, 1993;Liferman et al, 1994), was counted every two weeks during the therapy. The SCORAD index decreased at 2 weeks after hospitalization and then continued to decline slowly up to 8 weeks as shown in Fig.…”
Section: Eosinophils Decreased Prior To Clinical Improvementmentioning
confidence: 99%
“…There are no biochemical markers for atopic dermatitis, but patients typically have elevated serum IgE levels, eosinophil counts, and lactate dehydrogenase concentrations. [1][2][3][4] Topical corticosteroids are the standard treatment for acute lesions of atopic dermatitis. However, they carry a risk of local side effects such as skin atrophy and striae and systemic side effects.…”
mentioning
confidence: 99%
“…96,97 Although, human eosinophils express several chemokine receptors including CCR2, CCR3 and CXCR4, most studies have indicated the importance of CCR3 in the development of human AD and mouse models of AD. The ligands associated with CCR3 linked to the development of human AD include CCL5, CCL11, CCL13 and CCL26.…”
Section: Eosinophilsmentioning
confidence: 99%